Solve 5x - 2(2x - 7) = 2(3x - 1) + 7/2

Solution:

Given 5x – 2(2x – 7) = 2(3x – 1) + 7/2

=> 5x – 4x + 14 = 6x – 2 + 7/2

=> x – 6x = -14 -2 + 7/2

=> -5x = -16 + 7/2

=> -5x = (-32+7)/2 

=> -5x = -25/2

=> x = 25/10

=> x = 5/2

Was this answer helpful?

 
   

0 (0)

(1)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question